Parental Acceptance and Preferences Regarding Advanced Versus Basic Behavior Management Techniques in Pediatric Dentistry: A Systematic Review and Meta-Analysis of Observational Studies from the Middle East - Faisal Abed; Khlood Baghlaf; Shahad N. Abudawood; Heba Jafar Sabbagh (Healthcare, 2026)
Objective: The aim of this systematic review was to evaluate evidence comparing parental acceptance and preferences of advanced behavior management techniques with basic behavior management techniques among pediatric dental populations in the Middle East. Methodology: A systematic review and meta-analysis of observational studies was conducted in accordance with PRISMA 2020 guidelines and registered with PROSPERO (CRD420261294758) in February 2026. The systematic review included studies published between January 2015 and February 2026, identified through PubMed, Cochrane Library, Web of Science, ScienceDirect, and Google Scholar. Inclusion criteria encompassed observational studies assessing parental acceptance of behavior guidance techniques for healthy children aged 2–14 years, conducted in the Middle East. Two authors independently selected the studies and extracted the data. The risk of bias was assessed independently by two reviewers (F.A. and K.B) using an adapted Newcastle–Ottawa Scale (NOS), with any uncertainties resolved through discusscoion with a third reviewer (H.J.S.). Comparing the different behavior-guided techniques allowed for the creation of pooled effect estimates for the included studies. Result: A total of 88 studies were identified from the database search. Of the 88 studies identified, 11 met the inclusion criteria. Eleven cross-sectional observational studies were conducted in Iran, Turkey, Saudi Arabia, Bahrain, Egypt, Jordan, and Kuwait. The TSD approach consistently garnered the highest parental acceptance, ranging from 88% to 98%. In contrast, advanced methods like GA and physical restraint were the least preferred. Six meta-analyses were conducted across four clinical comparisons. Parental acceptance of GA was significantly lower than TSD (OR = 0.03, 95% CI: 0.02–0.07, p < 0.00001), as was parental preference (OR = 0.08, 95% CI: 0.05–0.15, p < 0.00001), with an overall pooled OR of 0.04 (95% CI: 0.02–0.08) and a complementary continuous analysis (SMD = −1.03, 95% CI: −1.54 to −0.51). Similarly, parental acceptance of protective stabilization was significantly lower than TSD (OR = 0.10, 95% CI: 0.06–0.15, p < 0.00001), as was parental preference (OR = 0.05, 95% CI: 0.03–0.08, p < 0.00001), with an overall pooled OR of 0.07 (95% CI: 0.05–0.11) and SMD of −1.87 (95% CI: −2.32 to −1.43). Comparisons involving N2O demonstrated extreme heterogeneity (I2 = 95%), precluding reliable pooled estimates. Acceptance of N2O varied more, influenced by regional differences and contextual factors. Conclusions: Middle Eastern populations of parents were consistently less accepting of advanced behavior management techniques, especially GA and protective stabilization, compared with TSD. These results are considered preliminary and are mainly based on cross-sectional studies and should be interpreted in the context of moderate risk of bias and substantial heterogeneity across the included studies. There is a need for more high-quality, longitudinal, multicenter studies to improve the evidence base for culturally sensitive behavior guidance in pediatric dental practice.